HUBUNGAN ANTARA STATUS GIZI DENGAN TINGKAT KEBUGARAN JASMANI PADA SISWI SMK NEGERI 1 SURABAYA KELAS X TAHUN AJARAN 2012-2013 - RIDWANDA, ABDI (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Physical education, sport and health (penjasorkes) give opportunity to student to directly involved on various learning experience through physical activities, playing and doing sport that done systematically. Beside physical activity, to support motion activity is by the nutrient sufficiency. The sufficiency of nutrient support student development and growth, whether physic development or psychology. Nutrition status is a measure of someone nutrient condition, nutrient sufficiency obtained from daily foods, good nutrient status will reflect good physic quality. Poor nutrient status will reflect bad physic quality and will affect physical fitness level. This research aim to find out correlation between nutrient status and the physical fitness level on tenth grade student of SMK Negeri 1 Surabaya and to find out how big the role of nutrient status to their physical fitness. The type of research is qualitative research with corelational method. Instrument that applied to measure physical fitness using MFT and for nutrient status using IMT/U. data analysis using contingency coefficient. Based on the research result its obtained that student who have poor nutrient status (thin) are of 7 students and have poor physical fitness, likewise to student who have poor nutrient status (fat) are of 12 students and have poor physical fitness, student who have obesity as big as 2 students and have very poor physical fitness, while student who have normal nutrient status is of 49 students (26 students have lack physical fitness level and 23 students have very lack fitness level). Data calculation result using SPSS 20.0 show value result as big as 0.416 and sig 0.002. it show that sig (0.002) < alpha 0.005, that mean Ho is rejected and H1 is accepted.  Thus, from the research result it can be known that nutrient status related with physical fitness especially to tenth grade student of SMK Negeri 1 Surabaya school year 2012-2013. Keywords : Penjasorkes, Nutrition status, Physical fitness.